Foraminifera biostratigraphy and paleoenvironmental studies of well-x, eastern Niger delta - Ibukunoluwa Adeola, Samuel; Adewole Adeola, John; Abiola Dairo, Victoria (International Journal of Advanced Geosciences, 2021)
Ditch cutting samples from Well-X drilled in the Eastern part of the Niger delta were subjected to biostratigraphy and paleoenvironmental studies using micropaleontological analysis to identify the foraminifera present in the sections penetrated by the well.A total of 50 (fifty) foraminifera species made up of benthonic and planktic spp were recovered from the sections. The marker species identified are Globorotalia acostaensis, Globorotalia mernadii cultrate, Neogloboquadrina dutertrei, Globorotalia plesiotumida, Globorotalia obesa, Globorotalia nepenthes, Sphaeroidinella subdehiscens, Neogloboquadrina dutertrei, Globigerinoides sudquadratus.The four (4) biozones identified are N16 (Late Miocene 9.5Ma - 10.9Ma), N15-N14, N13-N12 and N12-N11 (Middle Miocene with corresponding ages 10.9Ma -11.8Ma, 11.8Ma-12.2Ma and 12.2Ma respectively).Using the encountered benthonic foraminiferal species, the paleoecology was determined; and it was revealed that the paleoenvironment of the section ranges from Inner Neritic to Outer Neritic Environment. Also, the lithological analysis revealed an intercalation of Shale, Mudstone and Sand which indicates various paleoecological episodes that led to their deposition.The age of the well was inferred from the bioevents of the marker species to be Middle Miocene to Late Miocene with the sparse occurrence of the Calcareous Benthic and the Plankonic species suggesting a shallow marine environment.Â Â Â